State-of-the-art review of interface bond testing devices for pavement layers: toward the standardization procedure. Issue 2 (17th January 2017) - Rahman, Ali; Ai, Changfa; Xin, Chunfu; Gao, Xiaowei; Lu, Yang
Abstract: During the past thirty years, interface bonding between pavement layers has been a topical subject worldwide to research. In this context, many researchers have developed and utilized their own devices to investigate the properties of pavement interfaces. In the absence of an international standard procedure for interface bonding, it is inevitable that testing results are not comparable in all cases. In addition, various conducted studies reveal that parameters such as temperature, loading conditions, materials and so on exert an influence on interface properties. This paper aims to deal with the matter effectively via a thorough and comprehensive review of interface bond testing to lay the groundwork for standardization procedure. For this purpose, first, a general overview of interface bond function and its impact on pavement performance is presented. Then, different types of interface bond test methods according to loading conditions are explained; furthermore, the configuration of various setups is discussed and their function is compared together. Finally, given the prior experiences, a framework for a methodical approach to a standard evaluation of pavement interfaces is presented.